The New Figuration of Lola Fernández in 1976’s “Segunda Etapa: Cuarta escalera (serie Arquetipos)” (Second Stage: Fourth Ladder from the Series Archetypes) - Montero Rodríguez, Daniel Adolfo (2022)
This article is a semiotic study of the beginnings of neo-figuration in Costa Rican painting during the 1970s, with emphasis on the work Segunda Etapa: Cuarta escalera (serie Arquetipos) (1976) by the artist Lola Fernández Caballero. It is contextualized in the Salones Nacionales de Artes Plásticas in Costa Rica (1972). On the other hand, the notion of “neo-figurative art” is conceptualized as a theoretical approach. Likewise, a semiotic analysis is performed as a research method, interpreting the sign on three levels: syntactic, semantic and pragmatic. This way, it is perceived how the Costa Rican and Latin American context presents a change of social paradigm, a “values crisis”, through globalization and neoliberalism and, together with the promotion of Costa Rican art, it had a clear influence on the initialization process of Costa Rican neo-figuration, particularly in relation to the work analyzed in this article.